The Impact of Service Quality and Price on Customer Loyalty: The Role of Perceived Value as an Intervening Variable - Darmawan, Armin; Pujikharisma, Andi; Rapi, Amrin (Jurnal Teknologi dan Manajemen, 2025)
In today's highly competitive restaurant industry, customer loyalty is a vital component for achieving business success. However, many restaurants face challenges in retaining customers due to inadequate service quality and ineffective pricing strategies. This study explores the relationship between service quality and price on customer loyalty in a casual restaurant setting, with perceived value serving as a mediator. Utilizing Structural Equation Modeling (SEM) for data analysis, the results reveal that both service quality and price have a positive and significant impact on customer loyalty. Furthermore, perceived value is found to have a positive and significant effect on customer loyalty. The study also discovers that service quality and price significantly influence perceived value. These findings underscore the importance of service quality and price in fostering customer loyalty, as well as the crucial role of perceived value in this dynamic. By gaining a deeper understanding of these relationships, restaurants can devise strategies to enhance their service quality and pricing, ultimately leading to increased customer loyalty and business success. This study offers valuable insights for restaurants aiming to improve customer loyalty and retention, providing a foundation for informed decision-making and strategic development. The results of this research can be instrumental in helping restaurants to better understand their customers' needs and preferences, and to develop targeted strategies to meet those needs.